Tranzitujúce exoplanéty - Jánov, Richard; Zejda, Miloslav, 1965-; Masarykova univerzita. Přírodovědecká fakulta. Fyzikální sekce (2012)
Predložená bakalárska práca sa zaoberá štúdiom extrasolárnych planét pomocou metódy tranzitnej fotometrie. Metóda spočíva v meraní poklesu jasnosti v dôsledku prechodu planéty pred diskom materskej hviezdy. Cieľom práce je vykonať vlastné pozorovania niekoľkých tranzitov exoplanét a získané dáta použiť k spresneniu parametrov exoplanét.
The aim of the presented bachelor’s thesis is to study extrasolar planets via the method of transit photometry. The method is based on detection of a decrease in brightness of a star caused by a planet moving across the disk of the stellar primary. The goal of my work is to perform my own observations of a number of transits of extrasolar planets and use the acquired data to specify the parameters of extrasolar planets.
Vedoucí práce: Miloslav Zejda
Bakalářská práce (Bc.)--Masarykova univerzita, Přírodovědecká fakulta, 2012
Keywords: exoplanety; planetární astronomie; exoplanets; planetary astronomy; bakalářské práce; bachelor's theses